Balance and Gait Outcomes Following Four Square Step Exercise in Transtibial Amputees: Implications for Prosthetic Rehabilitation - Nugroho, Surya Adi; Syafi'ie, Hisyam; Ningsih, Cica Trimandasari; Setyawan, Dwi (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: This amputation not only affects the ability to walk but can also lead to a loss of sensory receptors in the somatosensory system, increasing the risk of falls. Research shows that transtibial prosthesis users often experience instability and difficulty maintaining balance, which can compromise their ability to walk safely. Effective rehabilitation methods are crucial for enhancing balance and reducing the risk of falls in individuals using transtibial prostheses. Four Square Step Exercise (FSSE). Objectives: The purpose of this study was to investigate the effect of the Four Square Step Exercise on walking balance in individuals using transtibial prostheses. Methods: This quasi-experimental study employed a one-group pre-test and post-test design to analyze the data, aiming to provide strong evidence of the effectiveness of FSSE in improving balance. Results: Statistical tests using a paired sample t-test yielded a p-value of <0.05, and a decrease in mean values from the pre-test to the post-test was observed. Conclusion: These findings provide strong evidence that individualized physical interventions can significantly reduce the risk of falls and improve the quality of life for individuals with lower limb amputations. Keywords: Four Square Step Exercise, Walking Balance, Transtibial Prosthesis